Morphological Diversity and Evolution of the Jugal in Dinosaurs. Issue 1 (January 2017) - Sullivan, Corwin; Xu, Xing
ABSTRACT: In dinosaurs, as in other reptiles, the homologue of the mammalian zygomatic bone is the jugal. The dinosaurian jugal was primitively triradiate, with posterior, dorsal and anterior processes that respectively contacted the quadratojugal, the postorbital, and the maxilla and lacrimal. However, the jugal evolved along different lines in the three major dinosaurian clades. In theropods this cranial element remained relatively conservative in morphology, apart from being reduced to a rod‐like structure in most birds and a few non‐avians. In sauropodomorphs the jugal eventually became small, plate‐like and nearly restricted to the area below the orbit, even being excluded from the ventral margin of the skull in many derived taxa. Among ornithischians the jugal was highly variable, but in many cases became large and/or adorned with ornamental features such as horns, flanges, and rugosities. The jugal does not appear to have been a site of muscle attachment in most non‐avian dinosaurs, but represented an important structural element in the akinetic dinosaurian skull. The conspicuous jugal ornaments seen in many ornithischian dinosaurs, like the less striking ones documented in some saurischians, may have played an important role in the social behavior of the species that possessed them. In many cases they have a weapon‐like aspect suggesting use in aggressive displays, if not actual combat, adding to the evidence that agonistic behavior was likely widespread among ornithischians in particular. Anat Rec, 300:30–48, 2017. © 2016 Wiley Periodicals, Inc.